Spin-Torque Oscillator Based on Magnetic Domain and Meron - Lv, Gang; Zhang, Hong; Cao, Xuecheng; Gao, Feng; Li, Guihua; Sun, Fengwei; Hou, Zhiwei; Liu, Yaowen (Frontiers in Physics, 2022)
In this work, micromagnetic simulations demonstrate that a steady oscillation mode accompanied by magnetic domain splitting and the creation and annihilation of meron can be excited by spin-polarized currents. It is found that the in-plane magnetic anisotropy and Dzyaloshinskii-Moriya interaction (DMI) have a greater influence on the oscillation frequency. The oscillation frequency can vary from 3 GHz to 31 GHz by controlling anisotropy strength under a fixed current density. By changing DMI strength, the oscillation frequency varies from 9 to 13.6 GHz and from 29.7 to 37 GHz. Compared with ferromagnetic skyrmion-based spin-torque oscillators (STOs), the STOs based on this magnetic domain and meron further increase the oscillation frequency. Our results may provide theoretical support for the research and development of future high-frequency STOs.